2022
DOI: 10.3389/fcell.2022.765062
|View full text |Cite
|
Sign up to set email alerts
|

A Complement-Related Gene Signature for Predicting Overall Survival and Immunotherapy Efficacy in Sarcoma Patients

Abstract: The prognoses of sarcomas are poor and the responses of them to systemic therapies are limited and controversial. Thus, there is an urgent need to stratify the risk factors and identify the patients who may benefit from systemic therapies. Here, we developed a reliable, complement-based gene signature to predict the prognosis of sarcoma patients. Survival-related complement genes were identified by univariate Cox analyses and were used to build a gene signature, which was further selected using the least absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Dancsok et al observed that a high CD56 + score was linked to significantly worse OS in mutation- and/or copy number-driven sarcomas (including WDLPS and DDLPS) while the overall CD56 expression in this cohort was remarkably low [ 86 ]. In contrast, a high NK cell-related gene signature was associated with a significantly prolonged OS in the TCGA-SARC cohort (including DDLPS) as confirmed by two independent studies [ 101 , 105 ]. However, a separate analysis of the histological subtypes within the TCGA-SARC cohort revealed that a NK cell signature was not significantly correlated with DSS in DDLPS [ 90 ].…”
Section: Lps-infiltrating Immune Cell Subsets and Their Clinical Sign...supporting
confidence: 54%
See 1 more Smart Citation
“…Dancsok et al observed that a high CD56 + score was linked to significantly worse OS in mutation- and/or copy number-driven sarcomas (including WDLPS and DDLPS) while the overall CD56 expression in this cohort was remarkably low [ 86 ]. In contrast, a high NK cell-related gene signature was associated with a significantly prolonged OS in the TCGA-SARC cohort (including DDLPS) as confirmed by two independent studies [ 101 , 105 ]. However, a separate analysis of the histological subtypes within the TCGA-SARC cohort revealed that a NK cell signature was not significantly correlated with DSS in DDLPS [ 90 ].…”
Section: Lps-infiltrating Immune Cell Subsets and Their Clinical Sign...supporting
confidence: 54%
“…Zhu and Hou showed that CD8 + T cell and Treg gene signatures were significantly associated with prolonged OS [ 104 ]. A third study reported no significant correlation between both CD8 + T cells and Tregs and OS [ 105 ]. Regarding publicly available transcriptome databases, the composition of the patient cohort and, most importantly, the applied gene signatures may vary among the studies and thereby cause conflicting results that are based on the same initial dataset.…”
Section: Lps-infiltrating Immune Cell Subsets and Their Clinical Sign...mentioning
confidence: 99%